Relevant advances in bone lengthening research: a bibliometric analysis of the 100 most-cited articles published from 2001 to 2017. Issue 5 (September 2019) - Mohedano, Alba; Castillo, Ana; de Pablos, Julio; Barrios, Carlos
Abstract : This study aimed to assess the scientific production of bone lengthening research by identifying the most-cited papers. All articles including the term 'bone lengthening' published between 2001 and 2017 were retrieved through the Web of Science database. The 100 most-cited articles on bone lengthening included a total of 4244 citations, with 414 (9.7%) citations in 2017. There was an average of 249.6 citations per year. The articles predominantly addressed biomechanics and bone formation (38). Different surgical techniques, including intramedullary nail (14), Ilizarov (nine), intramedullary skeletal kinetic distractor (ISKD) (six), Taylor spatial frame (6), the PRECICE device (three), and lengthening and submuscular locking plate (three), were the second most-studied topic. Most studies were therapeutic (58), whereas 30 studies were experimental investigations using animal models. Among the clinical studies, case series were predominant (level of evidence IV) (57). This study presents the first bibliometric analysis of the most relevant articles on bone lengthening. The list is relatively comprehensive in terms of identifying the top issues in this field. However, the most influential clinical studies have a poor level of evidence, although a slight tendency toward a better level of evidence has been observed in more recent years.